Effects of Nitrogen Addition on Soil Carbon-Fixing Microbial Diversity on Different Slopes in a Degraded Alpine Meadow - Li, Chengyi; Li, Xilai; Shi, Yan; Yang, Yuanwu; Li, Honglin (Frontiers in Plant Science, 2022)
Autotrophic carbon-fixing bacteria are a major driver of carbon sequestration and elemental cycling in grassland ecosystems. The characteristics of the response of carbon-fixing bacterial communities to nitrogen addition in degraded alpine meadows is unclear. In this study, we investigated the effects of three levels of nitrogen addition (LN, 2 g N·m-2·a-1, MN, 5 g N·m-2·a-1 and HN, 10 g N·m-2·a-1) on soil carbon-fixing bacteria in a degraded meadow on different slopes in the Yellow River source area of the Qinghai-Tibet Plateau. The results showed that there were significant differences in the abundance of some low abundance genera of carbon-fixing bacteria on the same slope (P<0.05), while there were no significant differences in the abundance of various phyla and dominant genera of carbon-fixing bacteria. Middle nitrogen addition on gentle slopes significantly reduced the Chao1 index and observed species (P<0.05), whereas nitrogen addition on steep slopes had no significant effect on the diversity. The abundance of the Cyanobacteria phylum and 28 genera of identified carbon-fixing bacteria differed significantly between slopes (P<0.05), and observed species of carbon-fixing bacteria was significantly higher on steep slopes than on gentle slopes (P<0.05). Factors affecting the carbon-fixing bacteria community structure include slope, N addition, ammoniacal nitrogen (N-NH4+), microbial carbon (MBC), soil water content (SWC), pH, soil C:N, microbial C:N. Slope, N addition, soil physicochemical properties, microbial biomass, and stoichiometric ratio did not significantly affect the carbon-fixing bacteria diversity. Thus, the effect of exogenous N addition on carbon-fixing bacteria in degraded alpine meadows was dependent on slope conditions, and the response of carbon-fixing bacteria abundance and species number to N addition on gently sloping sites was threshold-limited.